Anomalous passive subsidence of deep‐water sedimentary basins: a prearc basin example, southern New Caledonia Trough and Taranaki Basin, New Zealand. (3rd July 2013) - Baur, Jan; Sutherland, Rupert; Stern, Tim
Abstract Stratigraphic data from petroleum wells and seismic reflection analysis reveal two distinct episodes of subsidence in the southern New Caledonia Trough and deep‐water Taranaki Basin. Tectonic subsidence of 2.5 km was related to Cretaceous rift faulting and post‐rift thermal subsidence, and 1.5 km of anomalous passive tectonic subsidence occurred during Cenozoic time. Pure‐shear stretching by factors of up to 2 is estimated for the first phase of subsidence from the exponential decay of post‐rift subsidence. The second subsidence event occured 40 Ma after rifting ceased, and was not associated with faulting in the upper crust. Eocene subsidence patterns indicate northward tilting of the basin, followed by rapid regional subsidence during the Oligocene and Early Miocene. The resulting basin is 300–500 km wide and over 2000 km long, includes part of Taranaki Basin, and is not easily explained by any classic model of lithosphere deformation or cooling. The spatial scale of the basin, paucity of Cenozoic crustal faulting, and magnitudes of subsidence suggest a regional process that acted from below, probably originating within the upper mantle. This process was likely associated with inception of nearby Australia‐Pacific plate convergence, which ultimately formed the Tonga‐Kermadec subduction zone. Our study demonstrates that shallow‐water environments persisted for longer and their associated sedimentary sequences are hence thicker than would be predicted by any rift basin model that produces such large values of subsidence and an equivalent water depth. We suggest that convective processes within the upper mantle can influence the sedimentary facies distribution and thermal architecture of deep‐water basins, and that not all deep‐water basins are simply the evolved products of the same processes that produce shallow‐water sedimentary basins. This may be particularly true during the inception of subduction zones, and we suggest the term 'prearc' basin to describe this tectonic setting.